New thematic areas mainstreamed into Burkina Faso Rural sector development plan through CCAFS scenario work - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
As part of its scenario project implementation in West Africa, CCAFS has helped formulate the new National Plan for the Rural Sector of Burkina Faso (2016-2020). National experts and policy makers tested the plan against diverse socio-economic/climate scenarios up to 2050. This allowed for the definition of 22 actionable recommendations that were translated into new specific or thematic climate change and climate-smart agriculture actions mainstreamed into the new plan.